Family Support With Life Quality In Patients With Failure To Convert Heart - Enceng Herawati; Aszrul AB; Andi Baso Tombong (Comprehensive Health Care, 2019)
Patients with heart failure already have problems that will affect the quality of life, one of which can be influenced by family support. This study aims to determine the relationship of family support with quality of life in patients with congestive heart failure in H. Andi Sulthan Daeng Radja Hospital Bulukumba District. This study is an analytic observational study with a cross-sectional approach. Sampling was done by consecutive sampling technique. The population in this study were 144 patients with congestive heart failure at H. Andi Sulthan Daeng Radja Regional General Hospital. The sample in this study were 48 people. The measuring instrument used is a questionnaire. Data analysis using the Chi-Square test. The results of the study showed that from 21 respondents who received good family support there were 16 (57.14) whose quality of life was poor and 5 (25%) of good quality. And from 27 respondents who received family support in the poor category, there were 12 (42.85%) of poor quality of life, and 15 (75%) of good quality. Based on the results of the analysis of family support with quality of life using the Chi-Square statistical test obtained p = <0.027 <0.5 indicates that there is a relationship between family support and quality of life in congestive heart failure patients at H. Andi Sulthan Daeng Radja Hospital Bulukumba District.